Healing South African Wounds - (:unkn) unknown (My University, 2009)
On the eve of the democratic elections scheduled in South Africa in 2009, this collection of essays analyses the many ways in which South Africans have been trying to heal the wounds of apartheid, as advocated in Nelson Mandela’s famous 1994 speech, delivered at the dawn of the ‘ new ’ South Africa. The articles encompass such diverse fields as politics, literature, cinema, welfare policies or education, and they all seek to explore the sea change which totally reshaped South African identity in the last fifteen years that followed the demise of apartheid. The notion of ‘ healing the wounds’ is used both as a pretext and as a focal point to build up as complete a picture as possible of South Africa today. The specificity of the collection is to define healing as an ongoing process whose result seems to remain a rather elusive goal.
Keywords: African Research